1998
DOI: 10.1042/bj3310489
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of kinases impairs neutrophil activation and killing of Staphylococcus aureus

Abstract: Intracellular phosphorylations polymorphonuclear neutrophils are mediated by kinases, including mitogen activated-protein (MAP) kinases and phosphatidylinositol 3-kinase. In the present study we demonstrate their effector functions upon both ligation of cell-surface seven-transmembrane-spanning receptors by bacterial peptide formylmethionyl-leucylphenylalanine as well as in the process of destruction of Staphylococcus aureus. To regulate neutrophil MAP kinases p38 and p44/42, specifically, we made use of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 47 publications
(45 reference statements)
5
51
1
Order By: Relevance
“…In our experiments we have observed that LPS-induced Rac activation occurs within less than 1 h of LPS stimulation, whereas enhanced phagocytosis of bacteria occurs after 12 tosis and chemotaxis [25][26][27]. A previous study even shows that CpG regulates the phagocytosis of bacteria through p38 [13].…”
Section: Discussionmentioning
confidence: 89%
“…In our experiments we have observed that LPS-induced Rac activation occurs within less than 1 h of LPS stimulation, whereas enhanced phagocytosis of bacteria occurs after 12 tosis and chemotaxis [25][26][27]. A previous study even shows that CpG regulates the phagocytosis of bacteria through p38 [13].…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, in this study, a brief (15 min) period of reoxygenation restored both ROS formation and bactericidal capacity. Inhibition of neutrophil ROS production by selective inhibitors of p38 and p44/42 MAPK has also been shown to decrease S. aureus killing, although these inhibitors additionally reduced mobilisation of b 2 integrin to the plasma membrane, which may have contributed to the effect [89]. Neutrophils isolated from patients suffering recurrent pyogenic infections showed a strong correlation between impaired S. aureus killing and reduced superoxide anion production [90], and neutrophils from patients with chronic granulomatous disease (where ROS generation is absent) had significantly impaired ability to kill S. aureus [32].…”
Section: Hypoxic Effects On S Aureus and Its Killing By Neutrophilsmentioning
confidence: 99%
“…These MAP kinases have an essential role in PMN intracellular signaling pathways in response to various external stimuli and environmental stresses (15,31,55). The p38 MAP kinase pathway is responsible for PMN superoxide generation, chemotaxis, and IL-8 production in response to TNF-␣ and FMLP, and the activation of MAP kinase pathways generally results in activation of transcription factors which regulate protein synthesis (36,55). The p38 MAP kinase pathway is involved in PMN apoptosis and gene expression (11,55).…”
Section: Discussionmentioning
confidence: 99%
“…The activities of p38 and extracellular signal-related kinase (ERK 1/2, p44/42) increase rapidly in response to N-formyl-methionyl-leucyl-phenylalanine (FMLP) or lipopolysaccharide, suggesting that these kinase cascades have a pivotal role in regulating PMN function (7,24). The intracellular signaling pathways which regulate key PMN functions have been partially characterized, but the extent to which they contribute to PMN activation by GBS is undefined (5,36).…”
mentioning
confidence: 99%